Research on machining technology of complex structure parts of high-speed train body. Issue 1 (January 2021) - Chen, H H; Meng, F J; Zhang, D S; Miao, L Q; Qiao, H; Sang, M; Qian, D M; Wang, W B
Abstract: According to the high-speed train body chassis connecting plate and the side wall key piece structure is complex, the processing difficulty is big, the processing is easy to deform, the precision is not easy to control, the processing efficiency is low, carries on the processing craft characteristic analysis, produces the processing craft analysis report. The dynamic milling forces in X, Y and Z directions during milling process are tested by means of testing and analyzing the dynamic characteristics of the machine tool, and the dynamic performance of the system can be tested by means of modal test, the transfer function of the system is obtained, and the modal parameters such as natural frequency, damping ratio and modal stiffness are obtained by mode fitting on the basis of the transfer function data, complete the dynamic characteristic analysis of the machine tool. Based on the modal analysis of the whole process system and the dynamic model analysis of the milling process, the chatter stability region of the milling process is simulated by using the theory of regenerative chatter, the results of chatter stability region related to milling process parameters are given.